AN ANALYSIS FIGURATIVE LANGUAGE IN THE SHORT STORY “Tale-Tell Heart” - Dewi Karimah; Lux Anggraeni; Nurina Rahmah Hayuningtias; Rahma Putri Yunia (Center of Language and Cultural Studies, 2022)
This study aims to analyze the types of figurative language contained in the short story